(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Without a doubt, covid-19 caused the global trade to a standstill and price of oil to fall unprecedently. Contrary to the common belief, people are concerned about the severity of the disease and started wearing gloves. The demand for glove has increased. This study focuses on selected factories which uses existing technologies to produce gloves. Owing to the demand, gloves are exported, thus ensuring sustainable business growth. These factories use their existing machines to produce gloves. It is noted that inhouse mechanical and chemical engineers are working around the clock to innovate the existing machineries. Also, employees are encouraged to spearhead innovative ideas into the production lines. The qualitative analysis is used for this study. The finding of this paper reveals that during unprecedented times, the demand of gloves has increased globally, which concomitantly allowed locally owned companies to increase the production gloves. Ultimately, these companies are having a good time in harvesting profit and maintaining a sustainable business growth. These companies fully adhere to sustainable product and eco-friendly